2008
DOI: 10.1097/ftd.0b013e31817fd5ed
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Quetiapine in a Patient with a Massive Overdose

Abstract: We present a case of massive overdose with the atypical antipsychotic quetiapine in a 34-year-old woman (body weight 65 kg). At admission, approximately 2 to 4 hours after ingestion of approximately 24 g of quetiapine, the patient was comatose (Glasgow Coma Scale score 5), requiring orotracheal intubation and transfer to the intensive care unit. Because of myoclonic jerks and generalized seizures, benzodiazepines were administered. In addition to transient mild hypotension after intubation, the main cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…Both hypotheses might explain why mitragynine was still detectable in the urine after 2 weeks. Prolongation of elimination half-life has been described after overdoses of therapeutic drugs [27,28]. Unfortunately, the liver biopsy was too small to be analyzed for its content of M. speciosa alkaloids.…”
Section: Discussionmentioning
confidence: 99%
“…Both hypotheses might explain why mitragynine was still detectable in the urine after 2 weeks. Prolongation of elimination half-life has been described after overdoses of therapeutic drugs [27,28]. Unfortunately, the liver biopsy was too small to be analyzed for its content of M. speciosa alkaloids.…”
Section: Discussionmentioning
confidence: 99%
“…Where reported, the outcomes of the 107 cases ranged from recovery to death. Recovery from coma was reported in 4 cases . In a report of 18 quetiapine overdose cases, the outcome was not reported with the exception of 1 patient who recovered .…”
Section: Resultsmentioning
confidence: 97%
“…A study of quetiapine acute overdose (n = 945 cases) reported 96 comas and 3 deaths (∼10% and 0.3% of cases, respectively) . In addition, several case reports of quetiapine overdose describe reversible comas . In the index coma case the possibility of overdose of quetiapine or other substances was not mentioned, and the outcome was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the delayed occurrence of a seizure following overdose incident is peculiar in light of the pharmacokinetics of quetiapine. Other reports of seizure place the timing at 4–8 hours following quetiapine overdose [2, 7]. Plasma concentration of quetiapine typically peaks at 1–1.5 hours, and its elimination half-life is approximately 6 hours [8, 9].…”
Section: Discussionmentioning
confidence: 99%